Multiband optical variability of 3C 279 on diverse time-scales - Agarwal, Aditi (2019)
We have monitored the flat spectrum radio quasar, 3C 279, in the optical B, V, R, and I passbands from 2018 February to 2018 July for 24 nights, with a total of 716 frames, to study flux, colour, and spectral variability on diverse time-scales. 3C 279 was observed using seven different telescopes: two in India, two in Argentina, two in Bulgaria, and one in Turkey to understand the nature of the source in optical regime. The source was found to be active during the whole monitoring period and displayed significant flux variations in B, V, R, and I passbands. Variability amplitudes on intraday basis varied from 5.20 to 17.9 per cent. A close inspection of variability patterns during our observation cycle reveals simultaneity among optical emissions from all passbands. During the complete monitoring period, progressive increase in the amplitude of variability with frequency was detected for our target. The amplitudes of variability in B, V, R, and I passbands have been estimated to be 177 per cent, 172 per cent, 171 per cent, and 158 per cent, respectively. Using the structure function technique, we found intraday time-scales ranging from ∼23 min to about 115 min. We also studied colour–magnitude relationship and found indications of mild bluer-when-brighter trend on shorter time-scales. Spectral indices ranged from 2.3 to 3.0 with no clear trend on long-term basis. We have also generated spectral energy distributions for 3C 279 in optical B, V, R, and I passbands for 17 nights. Finally, possible emission mechanisms causing variability in blazars are discussed briefly.